DYNAMICS OF DRUG RESISTANCE IN M. TUBERCULOSIS DURING THE NEW CORONAVIRUS INFECTION PANDEMIC IN DUSHANBE: THE NEED FOR URGENT MEASURES - Z.KH. TILLOEVA (Avicenna Tajik State Medical University, 2022)
Objective: To study the frequency and structure of primary and secondary drug resistance in M. tuberculosis (MTB) and risk factors for primary multidrug/rifampicin resistance (MDR/RR) in MTB before (Group I: 2018-2019) and during the COVID-19 pandemic (Group II: 2019-2020) in Dushanbe in patients with pulmonary tuberculosis (PTB). Methods: A cohort retrospective study included all patients with PTB tested for susceptibility to anti-tuberculosis drugs (ATD). Odds ratio (OR), 95% confidence interval (95% CI), and p-value were used to determine the significance of the association between frequency and drug susceptibility spectrum (DSS) in groups I and II; risk ratio (RR) was applied to assess a possible association between exposure and outcome. Results: The study included 559 newly diagnosed and 87 previously treated patients. Primary MDR/RR MTB was found in 21.1%, secondary - in 39.8% of patients: in group I, patients with primary MDR/RR MTB constituted 22.4%, secondary - 34.7%; in group II, the prevalence of secondary MDR/RR MTB was found to be three times higher than that of the primary resistance (OR=2.97; 95% CI=1.67-5.27, p<0.001) due to a decrease in the prevalence of primary MDR/RR MTB (19.5%) and an increase in the secondary MDR/RR MTB (47.4%). There was a statistically significant increase in the frequency of primary drug resistance to fluoroquinolones in group II compared with group I: OR=2.58 for levofloxacin (p=0.003) and OR=2.31 for moxifloxacin (p=0.027). An increase in primary MDR/RR MTB was found among healthcare workers in group II (RR=3.21; 95% CI=1.50-6.89; p=0.05), which was statistically significant in patients with diabetes mellitus in both groups: group I (RR=1.83; p=0.035) and group II (OR=2.68; p<0.001). Conclusion: The current high prevalence of primary and secondary MDR, the increase in monoresistance during the COVID-19 pandemic, and the association of MDR with employment in healthcare institutions raise concerns regarding the quality of implementation of tuberculosis (TB) infection control measures in Dushanbe. The increased frequency of resistance to fluoroquinolones requires immediate action to control their prescription. It is recommended to improve anti-TB standards among patients with diabetes mellitus.